An inquiry into significant factors for accident prevention embodied in the Factories Act - Horne, Jerome (Department of Mechanical Engineering, 2016)
The Factories, Machinery and Building Work Act of 1941 has embodied in it certain factors which are apparently intended to promote the prevention of accidents in industry. These factors have been lifted out of the Act and Regulations and their significance is discussed in this thesis. The results of a questionnaire posed to firms are presented and analysed. These results indicate a limited degree of effective accident prevention which can be ascribed to the existence of the Factories Act. This thesis is divided into three parts: Part I : What the Factories Act provides for. Part II: The significant factors for accident prevention embodied in the Act. Part III: Conclusions and Recommendations. The history of the Factories Act is briefly traced and the Act in its present form is discussed in considerable detail. The following factors are revealed: - Registration for the purposes of control; - Approvals for the purpose of quality; - The creation of a safe and healthy environment; - The utilisation of competent persons; - The legal obligations of various classes of persons. Case histories of accidents are worked into the text to illustrate aspects under discussion. These are accidents which have been investigated by the Division of Occupational Safety of the Department of Manpower. Identifying features have been omitted. A limited comparison is made between the Factories Act and the British and American occupational safety acts. The proposed Machinery and Occupational Safety Draft Bill is discussed. It is concluded that there are factors for accident prevention embodied in the. Act. These are: legal registration, approvals, specific regulations, written appointments of competent persons, appointment of inspectors and accident enquiries. How effective these factors are, requires further statistical work. Certain recommendations are made which are intended to make the application of the Act more effective. A particular shortcoming of the Act is the small emphasis on training of persons in safety awareness. Greater provision should be made for such training and definite guidelines should be laid down in the Act for safety training of the worker. The Government has published a Machinery and Occupational Safety Draft Bill which retains many of the features of the present Act. If the positive factors discussed in this thesis are retained and added to during the passage of the new Bill through Parliament, industry and its workers should feel the benefits in the years ahead.